2011
DOI: 10.1111/j.1473-2165.2010.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Interest in cosmetic improvement as a marker for tanning behavior: a survey of 1602 respondents

Abstract: Dermatologists see many patients interested in improving their physical appearance through cosmetic procedures or medical means. Dermatologists frequently counsel patients on sun protection as well, particularly those with a personal or family history of skin cancer, sun-sensitive dermatoses or those with obvious sun damage. Our objective in this study was to identify novel markers of skin cancer risk which may aid dermatologists in targeting extra sun protection counseling for certain groups. A sixteen-questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Frequent tanners, regardless of their tanning methods, also showed stronger intentions to undergo plastic surgery procedures, which potentially pose a high risk to a person's health. This comparison also supports the previous finding that frequent tanners in general are more interested in improving their physical appearance through cosmetic procedures or medical means (Cathcart et al., ). Habitual tanners considered plastic surgery as necessary for an improved body image and self‐esteem.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Frequent tanners, regardless of their tanning methods, also showed stronger intentions to undergo plastic surgery procedures, which potentially pose a high risk to a person's health. This comparison also supports the previous finding that frequent tanners in general are more interested in improving their physical appearance through cosmetic procedures or medical means (Cathcart et al., ). Habitual tanners considered plastic surgery as necessary for an improved body image and self‐esteem.…”
Section: Discussionsupporting
confidence: 89%
“…Cathcart et al. () found that tanned individuals were significantly more interested in all aspects of their appearance. For example, dermatologists indicated that tanned patients were more interested in improving their physical appearance through cosmetic procedures (Cathcart et al., ).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Even dermatology patients with a history of skin cancer fail to use sunscreen adequately . There is evidence that sunscreen use is associated with reduced photoaging, and newer data have shown that appearance‐based messages are more effective than health‐based messages in promoting daily sunscreen use . Appearance‐based skin health motivators have also been found among adults…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion has also been supported by the recent study by Moers-Carpi et al,47 and by the head-to-head study that demonstrates similar efficacy when incobotulinumtoxinA and onabotulinumtoxinA are applied using a 1:1 unit conversion ratio 48. However, higher doses can be appropriate for subjects, usually men, who tend to have a larger muscle mass,28 and consensus guidelines for the treatment of glabellar frown lines emphasize the need to individualize treatment, recommending onabotulinumtoxinA dose ranges of 10–30 U for women and 20–40 U for men for glabellar frown lines 15…”
Section: Overview Of Current Strategies For the Management Of Glabellmentioning
confidence: 59%